Material and design strategies for chronically-implantable neural probes - Fei Liu; Tian-Ming Fu (NPG Asia Materials)
Abstract Implantable neural probes capable of monitoring deep brain activities with single-neuron resolution have contributed substantially to our understanding of brain function, treatment of neurological diseases, and application in brain-machine interface. However, conventional probes comprised primarily of rigid inorganic materials with large feature sizes face several limitations when being chronically implanted, including chronic recording instability, elevated immune responses within the brain, and deleterious neuron death. Driven by the strong desire for long-term stable brain interfaces and innovations in biomaterials and probe designs, novel neural probes are emerging and being rapidly adopted in academic and clinical settings. Here, we first review the historical progression of conventional implantable neural probes. We then discuss their limitations in long-term brain interfaces and the underlying biological mechanisms. Next, we summarize recent progress in next-generation chronically stable probe technologies enabled by materials innovations and structural engineering. Last, we highlight several outstanding challenges and future opportunities of the field. We argue that advancements in biomaterial engineering integrated with innovations in probe design and manufacturing will not only play an increasingly critical role in neuroscience and therapeutics but also offer a general approach to achieve long-term stable tissue monitoring by blurring the distinction between man-made devices and natural-born organisms.